Multidisciplinary Capstone Senior Design Projects: A Comparative Analysis of Industry-Sponsored and Faculty-Sponsored Projects Using Comprehensive Performance Metrics - Mohamed M. Morsy; Md. Nizam Uddin; Faycal Znidi (MDPI AG, 2024)
Engineering education has continually evolved to embrace Project-Based Learning (PBL), a dynamic classroom approach emphasizing learning through engagement in real-world projects. The study conducts a comparative analysis of multidisciplinary Capstone Senior Design Projects across Electrical Engineering, Mechanical Engineering, and Computer Science at Texas A&M University at Texarkana. The research emphasizes understanding the dynamics of student collaboration within these disciplines and scrutinizes the impact of industry and faculty sponsorship on these projects. The methodology involves a comprehensive comparative analysis, employing diverse performance metrics to evaluate the effectiveness of different sponsorship models. This approach aims to uncover the influence of these models on project outcomes and students' educational experiences. The results reveal notable differences between industry-sponsored and faculty-sponsored projects. Industry sponsorship leads to higher performance in overall project execution and professional skills development. In contrast, faculty-sponsored projects are more effective in nurturing teamwork and communication abilities among students. The findings suggest that each sponsorship type presents unique benefits and challenges. Industry-sponsored projects provide valuable hands-on problem-solving experience, though they may suffer from inconsistencies in mentorship and varying expectations. Faculty-sponsored projects offer a more stable and consistent educational environment but might lag slightly in performance metrics. Integrating elements from both sponsorship models could provide students with a more balanced and enriching learning experience.